On rare skate Bathyraja bergi Dolganov, 1985 from the waters of Russia with notes on its taxonomy - Vladimir N. Dolganov; Talija T. Ginanova (Известия ТИНРО)
Morphological description for 12 specimens of skate Bathyraja bergi caught in the North-West Pacific in 1978-2013. Plastic signs and counts for teeth, vertebras, pectoral fin, and intestinal valve are presented. There are at least subspecies differences between the skates B. bergi from the Japan Sea and eastern coast of Japan.